"Hazard Analysis Critical Method (Haccpm) Implementation Analysis On Scrap Reduction At Pt. Tci Garut'' - et. al., Titto Rohendra, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Efforts to produce products in accordance with consumer needs, companies are required to produce quality products. Commitment to product quality will have a positive impact and win the competition for companies, especially in the food sector. For that, it is necessary to standardize the quality management system that is globally recognized. Hazard Analysis Critical Method (HACCPM) is a method to ensure food safety by obtaining HACCPM certification from the food organization used by PT. TCI Garut is a guarantee of food safety. The HACCPM method can identify key points in the production process, and it can help reduce the number of defective products produced. The results of applying the HACCPM method, PT. TCI Garut obtained HACCPM certification to ensure the food safety of its products, and succeeded in reducing the number of defective products from an average of 2.21% before HACCPM application to 0.91% after HACCPM application. From the results of HACCPM application, these important points are caused by the danger of pollution and the danger of additives that can endanger the health of consumers.